The Effect of Product Quality, Promotion, and Brand Image on Purchasing Decisions (Case Study at Brand Image Fashion Stores in South Bengkulu) - Elvina Oktipianti; Sulisti Afriani; M. Rahman Febliansa (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The purpose of this study was to determine the effect of product quality, promotion and brand image on purchasing decisions at the Citra Baru Fashion Store, South Bengkulu. The sample in this study were 40 customers at the Citra Baru store, South Bengkulu. Data collection using a questionnaire and the method of analysis used is the validity test, reliability test, classic assumption test, and hypothesis testing.The results showed that the regression value Y = -4.033 + 0.250 (X1) + 0.384 (X2) + 0.669 (X3) with a positive regression direction means that product quality has a significant effect on purchasing decisions, because the significant value is 0.000 less than 0.05. That is, product quality will increase purchasing decisions at the new Citra Baru fashion store in Bengkulu Selatan. Promotion has a significant effect on the purchase decision of the new image fashion store in South Bengkulu, because the significant value of 0.000 is less than 0.05. That is, the promotion will increase purchasing decisions at the new image fashion store Bengkulu Selatan. Brand image has a significant effect on purchasing decisions, because the significant value of 0.000 is less than 0.05. That is, brand image will increase purchasing decisions at the new image fashion store in South Bengkulu. Product quality, promotion and brand image have a significant effect on purchasing decisions so that the initial hypothesis proposed is proven (Ha is accepted). That is, there is a significant influence on product quality, promotion and brand image on purchasing decisions together. The coefficient of determination R square is 0.813. This means that product quality, promotion and brand image affect purchasing decisions by 80% while the rest (100-80% = 20%) is influenced by other causal factors not examined in this study.